Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Extreme enriched-mantle (EM) compositions recorded by the Sr-Nd-Hf isotopes of global cratonic lamproites - Soumendu Sarkar; Hayden Dalton; Andrea Giuliani; David Phillips; D. Graham Pearson; Geoff M. Nowell; Jon D. Woodhead; Janet Hergt; Roland Maas; A. Lynton Jaques; N.V. Chalapathi Rao; Yaakov Weiss; et al. (Geochimica et Cosmochimica Acta, 2025)

The Pb, Sr and Nd isotopic composition of the upper continental crust: An Australian perspective - Candan U. Desem; Jon Woodhead; Patrice de Caritat; Roland Maas; David C. Champion; Anthony Dosseto; Ashlea Wainwright; Graham Carr (Chemical Geology, 2025)

Randomized trial in rural Native American homes heated with wood stoves: results from the EldersAIR study - Curtis W. Noonan; Ethan S. Walker; Erin O. Semmens; Annie Belcourt; Johna Boulafentis; Crissy Garcia; Jon Graham; Nolan Hoskie; Eugenia Quintana; Julie Simpson; Paul Smith; Howard L. Teasley; et al. (Air Quality, Atmosphere & Health, 2024)

Behavioral responses of two African mesopredators to human and non-human apex predators - Rebecca J. Welch; Craig J. Tambling; Graham I. H. Kerley; Armand D. Kok; Liaan Minnie; Jon M. Taylor; Jessica Comley; Dan M. Parker (Behavioral Ecology and Sociobiology, 2023)

Efficacy of commercial peroxyacetic acid on Vibrio parahaemolyticus planktonic cells and biofilms on stainless steel and Greenshell™ mussel (Perna canaliculus) surfaces - Dan Wang; Jon S. Palmer; Graham C. Fletcher; Stephen L.W. On; Dragana Gagic; Steve H. Flint (International Journal of Food Microbiology, 2023)

Comparative genome identification of accessory genes associated with strong biofilm formation in Vibrio parahaemolyticus - Dan Wang; Graham C. Fletcher; Dragana Gagic; Stephen L.W. On; Jon S. Palmer; Steve H. Flint (Food Research International, 2023)

Biofilm formation, sodium hypochlorite susceptibility and genetic diversity of Vibrio parahaemolyticus - Dan Wang; Graham C. Fletcher; Stephen L.W. On; Jon S. Palmer; Dragana Gagic; Steve H. Flint (International Journal of Food Microbiology, 2023)

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Differential effects of magnesium, calcium, and sodium on Listeria monocytogenes biofilm formation - Saili Chalke; Sinisa Vidovic; Graham C. Fletcher; Jon Palmer; Steve Flint (Biofouling, 2022)

In silico analysis revealing CsrA roles in motility-sessility switching and tuning VBNC cells in Vibrio parahaemolyticus - Dan Wang; Steve H. Flint; Dragana Gagic; Jon S. Palmer; Graham C. Fletcher; Stephen L. W. On (Biofouling, 2021)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Effiziente DNA-Extraktion aus geringen Probenmengen - Wiktoria Banczyk; Mary Loten; Jonelle Thompson; Jessica Seifarth; Jon Drobac; Erica K. Graham; Anupama Gopalakrishnan; Tanja Lopez (BIOspektrum, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

The Identification and Tracking of Uterine Contractions Using Template Based Cross-Correlation - Sarah C. McDonald; Graham Brooker; Hala Phipps; Jon Hyett (Annals of Biomedical Engineering, 2017)

Major zircon megacryst suites of the Indo-Pacific lithospheric margin (ZIP) and their petrogenetic and regional implications - Lin Sutherland; Ian Graham; Gregory Yaxley; Richard Armstrong; Gaston Giuliani; Paul Hoskin; Victor Nechaev; Jon Woodhead (Mineralogy and Petrology, 2016)

Towards fair local outcomes in adaptation to sea-level rise - Sonia Graham; Jon Barnett; Ruth Fincher; Colette Mortreux; Anna Hurlimann (Climatic Change, 2015)

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

A unified model for gold mineralisation in accretionary orogens and implications for regional-scale exploration targeting methods - Jon M. A. Hronsky; David I. Groves; Robert R. Loucks; Graham C. Begg (Mineralium Deposita, 2012)

Characterising modal metasomatic processes in young continental lithospheric mantle: a microsampling isotopic and trace element study on xenoliths from the Middle Atlas Mountains, Morocco - Jacqueline Malarkey; Nadine Wittig; D. Graham Pearson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2011)

Seasonality of arbuscular mycorrhizal hyphae and glomalin in a western Montana grassland - Emily R. Lutgen; Deborah Muir-Clairmont; Jon Graham; Matthias C. Rillig (Plant and Soil, 2003)

Methodological problems with ecstasy and the SCL-90 - Jon C. Cole; Harry R. Sumnall; Graham F. Wagstaff (Psychopharmacology, 2002)

Do slow‐growing species and nutrient‐stressed plants consistently respond less to elevated CO 2 ? A clarification of some issues raised by Poorter 1998) - Jon Lloyd; Graham D. Farquhar (Global Change Biology, 2000)